INVESTIGATION OF MYCOPLASMA SYNOVIAE SEROPREVALENCE IN BROILER BREEDER FARMS IN SOUTH BAČKA REGION - Milena Samojlović; Marko Pajić; Biljana Božić; Slobodan Knežević; Miloš Pelić; Dalibor Todorović; Sava Lazić (Archives of Veterinary Medicine, 2017)
Mycoplasma synoviae is known to cause respiratory disorders, synovitis, subclinical infections, air sacculitis and eggshell apex abnormalities in domestic poultry worldwide. Th e aim of this study was to determine M.synoviae seroprevalence in 5 diff erent broiler breeder farms in South Bačka from 2014 to 2017. A total of 1511 samples were tested using commercial indirect enzyme linked immunosorbent assay (ELISA) for detection of antibodies in the blood sera. In this study, the seroprevalence of 25.21% was found and 47 (40.87%) fl ocks out of 115 tested were positive to M.synoviae. Seroprevalence varied between 31.02% in 2015 and 16.78% in 2016. Flock prevalence ranged from 31.03% in 2014 to 55.88% in 2015. Th ese results suggest that M. synoviae infection is present in broiler breeder farms in South Bačka, and that is necessary to conduct further research, systematic monitoring and to improve biosecurity measures on broiler breeder farms.